Corruption case of Base Transceiver Station (BTS) in Indonesia: Framing analysis study of MediaIndonesia.com and Okezone.com - Ummah, Kuntum Chairum; Syarifudin, Achmad (C-DISC, 2023)
The BTS (Base Transceiver Station) construction corruption case of the Minister of Communications and Information, Johny G. Plate, who is also a cadre of the Nasdem Party, has caused a lot of debate among netizens. Online news portals with different party owners are also said to have an impact on the framing of reality and influencing readers' perspectives in viewing the BTS corruption issue. Therefore, it is necessary to further examine how the online media Mediaindonesia.com and Okezone.com framed the corruption case involving Johny G. Plate as the Secretary General of Nasdem Party and former Minister of Communication and Information. The method used in this research is the framing analysis proposed by Robert N. Entman. The subjects of this research are the online media news portals Mediaindonesia.com and Okezone.com, while the objects are news articles about the identification of Johny G. Plate (JP) as a suspect in the BTS Kominfo corruption case. The research results revealed that MediaIndonesia.com tends to view corruption cases with a positive frame by prioritizing the principle of presumption of innocence for not firing Johny G. Plate as Secretary General of the Nasdem Party. In contrast, Okezone.com tends to frame the news by supporting legal efforts to thoroughly investigate the case and supporting a number of DPP Perindo Party stances that seem to be framed as the stance of the news portal.